Implementing Cultural Policies With A View of Capacity-Building at University - Ghavamabadi, Ashraf; Salajegheh, Sanjar; Sheikhi, Ayyub; jalal Kamali, Mohammad (Cuestiones Políticas, 2020)
The increase in the level of awareness and knowledge of public officials and senior managers of the community about the need to formulate an appropriate public cultural policy indicates its role and importance in improving social life. This research was established with the main objective of identifying the components of the implementation of cultural policies. The descriptive survey was used methodologically and the data collection instrument was a questionnaire with the statistical population, including experts, which was carried out using the two-step Delphi method. The statistical population of experts included cultural managers and university professors in the field of management and policy formulation. The sampling was non-random and deliberate, with 7 interviews carried out. Based on Delphi's two-stage results, panel member consensus, and achievement of theoretical saturation, experts identified 44 components. In conclusion, the results also showed that the dimensions of "management factors" and "software" had the highest average and the dimensions of "structural factors" and "activation of cultural centers in the university" had the lowest range.